2005
DOI: 10.1186/1472-6874-5-8
|View full text |Cite
|
Sign up to set email alerts
|

Aberrations of TACC1 and TACC3 are associated with ovarian cancer

Abstract: BackgroundDysregulation of the human Transforming Acidic Coiled Coil (TACC) genes is thought to be important in the development and progression of multiple myeloma, breast and gastric cancer. Recent, large-scale genomic analysis and Serial Analysis of Gene Expression data suggest that TACC1 and TACC3 may also be involved in the etiology of ovarian tumors from both familial and sporadic cases. Therefore, the aim of this study was to determine the occurrence of alterations of these TACCs in ovarian cancer.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 44 publications
3
75
0
1
Order By: Relevance
“…Disturbances of centrosome function have also been implicated in tumorigenesis (Zyss and Gergely, 2009). Intriguingly, aberrations of TACC3 expression are associated with the etiology of ovarian, bladder and non-small-cell lung cancer (Lauffart et al, 2005;Jung et al, 2006;Kiemeney et al, 2010). Moreover, we have recently shown that the cellular outcome of mitotic stress induced by TACC3 depletion is decisively determined by the status of the post-mitotic G 1 checkpoint.…”
Section: Introductionmentioning
confidence: 99%
“…Disturbances of centrosome function have also been implicated in tumorigenesis (Zyss and Gergely, 2009). Intriguingly, aberrations of TACC3 expression are associated with the etiology of ovarian, bladder and non-small-cell lung cancer (Lauffart et al, 2005;Jung et al, 2006;Kiemeney et al, 2010). Moreover, we have recently shown that the cellular outcome of mitotic stress induced by TACC3 depletion is decisively determined by the status of the post-mitotic G 1 checkpoint.…”
Section: Introductionmentioning
confidence: 99%
“…5F-H). We had previously noted that TACC1 is expressed in the surface epithelium of the ovary (Lauffart et al, 2005) (Fig. 5F).…”
Section: Tacc1 Protein Expression In the Normal Human Reproductive Symentioning
confidence: 74%
“…1). We used a well-characterized specific antibody to TACC1 that identifies the mouse and human TACC1 proteins (Cully et al, 2005) and has been previously used for immunohistochemical procedures (Lauffart et al, 2005). Concentration matched rabbit IgG on a duplicate set of slides exhibited negative immunostaining (data available on request).…”
Section: Tacc1 Protein Expression During Mouse Embryogenesismentioning
confidence: 99%
See 2 more Smart Citations